(3eQGLYI fXe GdeMGSHI GdEdcJQhfjI (B/s - (3Gdajhej, eMeO eMeOs; (3GdedjLj, EHQGgje GdSjOs ((3GdEScfOQjI (B: s (3OGQ GdJYdje GdLGeYj(B, s)
(3JfGhd GdeDda HYV GdeLGdGJ GdeJbOeI deQGLYI fXe GdeMGSHI GdGdcJQhfjI ef NdGd (B9 (3aUhd bOe ef NdGdgG eaghe heGgjI hCgOGa hCgejI eQGLYI fXe GdeYdheGJ GdeMGSHjI GdcJQhfjG, HGdGVGaI Gdi CfhGY heYGjjQ hGLQGAGJ eQGLYI gPg GdfXe, cPdc GNJHGQGJ GdeQGLYI hGdQbGHI GdOGNdjI aj Vd eQGLYI fXe GdeYdheGJ GdGdcJQhfjI , hhGbY hGdBKGQ GdGjLGHjI GdYGdejI Ydi egfI GdeQGLYI aj eUQ haj GdCNjQ bOe HYV GdGSFdI hGdMGdGJ GdJWHjbjI(B. s
Keywords: (3eQGLYI GdMSGHGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s